ADAPTATION OF FOLK SONGS FOR THE ACAPPELLA CHOIR - J. Khodjayev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article describes the use of choral styles and tools of Central Asian peoples, folk and folk songs, depending on the melody, genre, content, as well as their national character, intonation and meter-rhythm structure. It also provides a brief overview of adaptations for two and more-voiced acappella choirs by arranging folk songs.